aac(6’)-Iaq, a novel aminoglycoside acetyltransferase gene identified from an animal isolate Brucella intermedia DW0551 - Lin, Naru; Xu, Wanna; Huang, Dawei; Liu, Chaoqun; Lu, Junwan; Zhu, Mei; Bao, Qiyu; Pan, Wei (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundBacterial resistance to aminoglycoside antimicrobials is becoming increasingly severe due to their use as commonly prescribed antibiotics. The discovery of new molecular mechanisms of aminoglycoside resistance is critical for the effective treatment of bacterial infections.MethodsBacteria in goose feces were isolated by plate streaking. The identification and characterization of a novel resistance gene from the bacterial genome involved various techniques, including molecular cloning, drug susceptibility testing, protein expression and purification, and enzyme kinetic analysis. Additionally, whole-genome sequencing and phylogenetic studies were performed.ResultsBrucella intermedia DW0551, isolated from goose feces, was resistant to 35 antibiotics, and the minimum inhibitory concentration (MIC) was particularly high for most aminoglycoside antibiotics. The novel aminoglycoside resistance gene aac(6’)-Iaq encoded by B. intermedia DW0551 conferred resistance to netilmicin, sisomicin, amikacin, kanamycin, gentamicin, tobramycin, and ribostamycin. The amino acid sequence of AAC(6’)-Iaq shared the highest identity (52.63%) with the functionally characterized aminoglycoside acetyltransferase AAC(6’)-If. AAC(6’)-Iaq contained all the conserved sites of the acetyltransferase family NAT_SF. The enzyme exhibited strong affinity and catalytic activity toward netilmicin and sisomicin. The mobile genetic element (MGE) was not found in the flanking regions of the aac(6’)-Iaq and aac(6’)-Iaq-like genes.ConclusionIn this work, a novel aminoglycoside acetyltransferase gene, designated aac(6’)-Iaq, which conferred resistance to a variety of aminoglycoside antimicrobials, was identified in an animal Brucella intermedia isolate. Identification of new antibiotic resistance mechanisms in bacteria isolated from animals could aid in the treatment of animal and human infectious diseases caused by related bacterial species.